Pranayama dalam Prenatal Yoga - I Putu Suyoga Hindhuyana; Putu Ayu Sri Kumala Dewi (UHN IGB Sugriwa Denpasar, 2021)
Pregnancy is an event that occurs in women which generally gives various changes in themselves. Along with the development of the fetus and increasing gestational age, a woman will certainly experience several changes such as physical changes, psychological changes, and social status of the mother. The changes that occur during pregnancy generally occur as symptoms and occur for most pregnant women. Either with, arise, or fear that is in itself, especially in pregnant women, one of the prenatal yoga exercises can be effectively overcome by doing pranayama exercises. During pregnancy, the body's needs are certainly different from the bodies of people who have never experienced the process of pregnancy. Likewise, with the need for pranayama exercises performed during pregnancy, which of course not all pranayama techniques can be practiced during pregnancy. There are several pranayama techniques that are good to practice during pregnancy, namely diaphragmatic breathing techniques, dirgha swasam breathing techniques, sitkari pranayama, sitali pranayama, bhramari pranayama, ujjayi pranayama, and anuloma viloma pranayama.